(Post-) Genomic approaches to tackle drug resistance in Leishmania. Issue 12 (12th March 2013) - BERG, MAYA; MANNAERT, AN; VANAERSCHOT, MANU; VAN DER AUWERA, GERT; DUJARDIN, JEAN-CLAUDE
SUMMARY: Leishmaniasis, like other neglected diseases is characterized by a small arsenal of drugs for its control. To safeguard the efficacy of current drugs and guide the development of new ones it is thus of utmost importance to acquire a deep understanding of the phenomenon of drug resistance and its link with treatment outcome. We discuss here how (post-)genomic approaches may contribute to this purpose. We highlight the need for a clear definition of the phenotypes under consideration: innate and acquired resistance versus treatment failure. We provide a recent update of our knowledge on the Leishmania genome structure and dynamics, and compare the contribution of targeted and untargeted methods for the understanding of drug resistance and show their limits. We also present the main assays allowing the experimental validation of the genes putatively involved in drug resistance. The importance of analysing information downstream of the genome is stressed and further illustrated by recent metabolomics findings. Finally, the attention is called onto the challenges for implementing the acquired knowledge to the benefit of the patients and the population at risk.